PEMERIKSAAN TEKANAN DARAH DAN PENDIDIKAN KESEHATAN TENTANG HIPERTENSI DI PASAR AIKMEL KABUPATEN LOMBOK TIMUR - Maruli Taufandas (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2020)
This science and technology-based community service (PBI) aims to provide insight into knowledge and understanding of the market traders of Aikmel, East Lombok Regency about Hypertension in market traders. The target of the science and technology-based community service (PBI) is the Aikmel market trader, East Lombok Regency. Submission of information about hypertension, especially in terms of preventing the occurrence of hypertension or high blood pressure is rarely done to market traders. This problem is solved by three stages of activities, namely: preparation, implementation, and evaluation. The preparation stage starts from the preparation of proposals, coordination with partners, preparation of tools and materials, and publication of invitations. The implementation is carried out by conducting blood pressure checks, and health education about hypertension, using the method of distributing leaflets and providing understanding to market traders. The evaluation was carried out by measuring blood pressure, to determine the success rate of blood pressure checks and health education about hypertension, the service conducted an interview survey of several market traders, market traders appreciated this activity well and were asked to carry out these checks regularly. The results of community service activities show a level of success with indications of a match between blood pressure checks, health education about hypertension according to the needs of Aikmel market traders, East Lombok Regency.